(3ahGFO GdQMdI hfJGFL GdSaQ aj JQGLe aVdGA GdbQf GdMGOj YTQs - (3GdTGaYqj, GdMehj Ke Gdecqj, eUWai Hf aJM Gddg, (B1123 (3g`s ((3eMeO Hf eUWai Hf aJM Gddgs)
(3ChdgG (B:s
(3HSe Gddg GdSjO GdMSf Hf GdEeGe GdbGSe Hf eMeO Hf Ydj cGf BjI ef BjGJ Gddg JYGi aj d NUdI CeG Gdabg acGf jYQag CMSf GdeYQaI hCeG GdfMh acGf ajg HGQYG hCeG HbjI GdYdhe s
(3BNQgG (B:s
(3GdSjO UdGM Hf CMeO Hf GdegOj GdeDjOj cGf ef eMGSf GdReGf heaGNQ GdChGf efbWY GdbQjf aj cd aVjdI hGdMGFR ef GdYdhe cd eSFdI LdjdI Edi aUGMI efWb SYI MaX Je GdLRA GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\238s
(3EjVGM Gdecfhf (B2\203s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs